A model-based approach to predict neuromuscular control patterns that minimize ACL forces during jump landing - Heinrich, D.; van den Bogert, A. J.; Csapo, R.; Nachbauer, W. (Computer Methods in Biomechanics and Biomedical Engineering, 2020)
Jump landing is a common situation leading to knee injuries involving the anterior cruciate ligament (ACL) in sports. Although neuromuscular control is considered as a key injury risk factor, there is a lack of knowledge regarding optimum control strategies that reduce ACL forces during jump landing. In the present study, a musculoskeletal model-based computational approach is presented that allows identifying neuromuscular control patterns that minimize ACL forces during jump landing. The approach is demonstrated for a jump landing maneuver in downhill skiing, which is one out of three main injury mechanisms in competitive skiing.